Effects of compression damage on mechanical behavior and quality attributes of apple fruit - Zhu, Jianjun; Zhu, Dequan; Wang, Li; Xue, Kang; Liao, Juan; Zhang, Shun (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2022)
Fresh apples are easily damaged during machining processing. To solve the compression damage of the apple, the impacts of compression damage and storage time on failure mechanical behavior and quality indexes of apple fruits were evaluated in this study, where the different compression forces (0, 40, 80, 160, 320, 640 N) were loaded on the equator position of apple fruits stored at 5 ± 0.5 °C for 16 days. Then, we investigated the damaged mechanical behavior, damage volume, weight loss, ethylene production, respiratory rate, firmness, browning degree, titratable acidity (TA), total soluble solids (TSS), TSS/TA rate, malondialdehyde (MDA), cell membrane permeability, ascorbic acid, total phenolic, total flavonoids, pectin and soluble pectin of apple were analyzed. The experiment results showed that the apple fruit will not be damaged, if the compressive force is less than 40 N. Compared with the 0 and 40 N groups, the weight loss of harvested apple fruit under compressive forces with 80, 160, 320, and 640 N significantly increased, while the browning degree, MDA, cell membrane permeability and soluble pectin firmness, ascorbic acid, total phenolic, total flavonoids and pectin decreased. In conclusion, in the process of post-harvest processing (picking, transportation, sorting, and packaging), the contact force between apple fruit and mechanical equipment should be limited to less than 40 N to avoid mechanical damage, and thus extending its shelf life and improving its commercial quality.